Blast response of a thin oriented strand board wall. (15th December 2019) - Hussein, Assal; Heyliger, Paul; Mahmoud, Hussam
Highlights: A new research trend considering simple blast protection wall systems for non-military applications. The blast pressure distribution in free-air and OSB wall response under blast load is presented graphically. The OSB wall showed a good capability to partially mitigate blast loading at extremely low cost. This study establishes a new concept in blast-resistant systems. It is not necessary to have high-tech sophisticated blast wall system to mitigate blast loading. Abstract: There has been a remarkable increase in the worldwide number of suicide bombing attacks in recent years. These attacks have left numerous victims as well as economic and psychological impacts on targeted locations. Developing new approaches to designing and constructing blast protection wall systems is an ever pressing need to partially mitigate the damaging effects of blast loadings. Several applications of simple blast protection wall systems have been considered for military purposes, but far fewer studies exist for non-military applications. The current study evaluates the overall performance of a thin oriented strand board (OSB) cantilever wall in response to the blast energy from explosive detonations. The study presents the results of open-space blast tests to measure the blast wave pressure in free air (without wall), and blast pressure (behind wall) at specified standoff distances. For the OSB response, a 3D dynamic finite element model was created using ABAQUS/Explicit software combined with the ConWep blast model to represent wall-blast wave interactions in free air to compare with the blast test results. Reductions in blast pressure behind the OSB wall of over 20 percent were observed. Good agreement between the test results and the numerical predictions was also found. The results of this work indicate the potential of using simple blast walls to partially mitigate blast loading at extremely low cost and minimal installation effort.